Dimensi Berkebinekaan Global dalam Kegiatan Gelar Karya P5 Tema Kearifan Lokal di SDN 02 Kota Bengkulu - Sanches, Luzzy Anne; Susanti, Atika (Universitas Bengkulu, 2026)
This research aims to describe the implementation and dimensions of global diversity in the exhibition activities of the Pancasila Student Profile Strengthening Project with a local wisdom theme in class V A SDN 02 Kota Bengkulu. The type of this research is qualitative research with a descriptive qualitative approach and descriptive method. The subjects in this study are the principal of SDN 02 Kota Bengkulu, the teacher who is the head of the P5 development team, the fifth-grade A teacher, and the fifth-grade A students of SDN 02 Kota Bengkulu. The research instrument uses observation guidelines, interviews, and documentation. Data analysis is conducted through data collection, data condensation, data display, and data verification. The technique for data validity is through triangulation and member check. The results of this study are in the form of the implementation of the P5 project exhibition activities, which consist of preparation, execution, and evaluation and reflection stages. The dimensions of global diversity consist of recognizing and appreciating cultures, communication and interaction between cultures, reflection and responsibility towards diversity experiences, and sosial justice. The conclusion of this research is that the implementation of the exhibition activities went smoothly and already reflects the dimensions of global diversity.